Monitoring Stations for Surface Water Quality - Qingren Wang; Yuncong Li; Thomas Obreza; Rafael Munzo-Carpena (EDIS)
The traditional approach to water quality monitoring involves manually sampling water at remote sites and transporting it to a laboratory for chemical analysis. New technology and instrumentation have improved our ability to monitor water quality continuously regardless of weather and accessibility. Specialized probes measure water quality parameters, electronic logging devices record and store data, and automatic samplers capture multiple water samples on either time or flow intervals. Telecommunication devices allow data to be downloaded remotely to an office or a laboratory, which makes site monitoring much easier, especially from remote locations. This document is Fact Sheet SL218, a publication of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2004.